COVID19: A Systematic Approach to Early Identification and Healthcare Worker Protection - Zhao, Yu; Cui, Chong; Zhang, Kun; Liu, Jialin; Xu, Jinfu; Nisenbaum, Eric; Huang, Yixiang; Qin, Guoyou; Chen, Bing; Hoffer, Michael; Blanton, Susan H.; Telischi, Fred; et al. (Frontiers in Public Health, 2020)
The COVID-19 outbreak and spread rapidly throughout globally with worldwide infections and deaths continuing to increase dramatically. To control disease spread and protect healthcare workers, accurate information is necessary. We searched PubMed and Google Scholar for studies published from December 2019 to March 31, 2020 with terms “COVID-19”, “2019-nCoV”, “SARS-CoV-2” or “Novel Coronavirus Pneumonia”. The main symptoms of COVID-19 are fever (83-98.6%), cough (59.4-82%), and fatigue (38.1-69.6%). However only 43.8% of patients have fever early in the disease course, despite still being infectious. These patients may present to clinics lacking proper precautions, leading to nosocomial transmission and infection of workers. Potential COVID-19 cases must be identified early to initiate proper triage and distinguish them quickly from similar infections. Early identification, accurate triage, and standardized personal protection protocols can reduce the risk of cross infection. Containing disease spread will require protecting healthcare workers.